2014
DOI: 10.1097/mbc.0000000000000095
|View full text |Cite
|
Sign up to set email alerts
|

Does incorporation of thromboelastography improve bleeding prediction following adult cardiac surgery?

Abstract: Cardiopulmonary bypass (CPB) coagulopathy increases utilization of allogenic blood/blood products, which can negatively affect patient outcomes. Thromboelastography (TEG) is a point-of-care measurement of clot formation and fibrinolysis. We investigated whether the addition of TEG parameters to a clinically based bleeding model would improve the predictability of postoperative bleeding. A total of 439 patients’ charts were retrospectively investigated for 8-h chest tube output (CTO) postoperatively. For model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Overall, our results show that only pFB and TEG‐MA were moderately associated with severe bleeding, although their predictive ability was far from optimal. This is in line with the findings of previous publications, which produced heterogeneous results regarding the predictive value of SLTs and viscoelastic tests for bleeding in critically ill patients with coagulopathy. Differences in design, clinical scenarios, and the time of sampling could partially explain these controversial results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, our results show that only pFB and TEG‐MA were moderately associated with severe bleeding, although their predictive ability was far from optimal. This is in line with the findings of previous publications, which produced heterogeneous results regarding the predictive value of SLTs and viscoelastic tests for bleeding in critically ill patients with coagulopathy. Differences in design, clinical scenarios, and the time of sampling could partially explain these controversial results.…”
Section: Discussionsupporting
confidence: 92%
“…The authors concluded that TEM could not predict which patients were at risk for major postoperative bleeding . In a retrospective study that included 439 patients undergoing cardiac surgery, the addition of TEG‐angle and MA did not improve the predictive ability of a well‐established previous clinical model based on age, preoperative use of clopidogrel, and other clinical variables to detect an increased postoperative chest tube output at 8 hour (75th percentile, 480 mL). Another similar study also found that TEG was not predictive of postoperative bleeding .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These settings include cardiac surgery [6770], liver transplantations [71], sepsis [72], trauma [7379], obstetrics [80], psychophysiological stress [81]. These systems have also been utilized to evaluate anticoagulant activity [82, 83] and determine what the critical threshold value is for the initiation of antifibrinolytic therapy in trauma [84].…”
Section: Thrombin Generation Assaysmentioning
confidence: 99%
“…Although salvaging will recover RBCs, it also removes platelets and coagulation factors, which can promote bleeding postoperatively [8]. We have associated increased CSB administration with increased postoperative bleeding [9]. Although studies demonstrate an independent association between blood transfusion and mortality, bleeding by itself may be harmful.…”
Section: Discussionmentioning
confidence: 98%